SOFTWARE AND SYSTEM INTEGRITY ASSESSMENT: A Comprehensive, Stop–loss Opportunity for Critical Infrastructures. Issue 4 (December 2016) - Ring, Jack
ABSTRACT: This article describes how the digital aspects of all critical infrastructures can evolve faster and be less vulnerable to cyber actions. Although focused on the US infrastructures it is applicable to all infrastructures world‐wide. The purpose is to motivate systems practitioners to become adept at software and system integrity assessment. We introduce the theory and method for discovering all logic, arithmetic, and semantic faults throughout an arbitrarily large, heterogeneous software suite. One version was initiated in the 1990's, proved effective in the marketplace but, being mostly manual, would not scale. Recently the principals of OntoPilot LLChttp://www.ontopilot.com have devised a significantly different way to assess system integrity that is amenable to automation. The balance of this article introduces the situation, highlights the system principles involved, considers the challenges in assessing software integrity, highlights the opportunity and value proposition, outlines the automation technology and finishes with a call to action. We recommend that certification in system integrity assessment be considered as a facet of the professional certifications offered by INCOSE, NDIA, IISE, and other professional and industry associations.